Inside Cover: A Fluorescent Guanosine Dinucleoside as a Selective Switch‐On Sensor for c‐myc G‐Quadruplex DNA with Potent Anticancer Activities (Chem. Eur. J. 35/2013). Issue 35 (19th August 2013) - Kumar, Y. Pavan; Bhowmik, Sudipta; Das, Rabindra Nath; Bessi, Irene; Paladhi, Sushovan; Ghosh, Rita; Schwalbe, Harald; Dash, Jyotirmayee
<x xml:space="preserve">Abstract</x> A fluorogenic guanosine‐dansyl conjugate (depicted) that detects G‐quadruplex DNA through fluorescence enhancement has been developed by J. Dash et al. and reported in their Communication on page 11502 ff. This dinucleoside interacts with both the external G‐quartets and in the groove regions of c‐myc G‐quadruplex DNA. It stains the nucleus preferentially and exhibits potent antiproliferative activities against the A375 human melanoma cell line.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>